Analysis of Dynamic Stresses of Pump-Turbine Runner during Load Rejection Process in Turbine Mode. Issue 1 (June 2021) - Chen, Funan; Yang, Xiaolong; Bi, Huili; Mao, Zhongyu; Luo, Yongyao; Liujingshi,; Fan, Hongang; Wang, Zhengwei
Abstract: During load rejection process, the rotation rate, head and discharge change a lot and the internal flow of the runner is complex, leading to fatigue cyclic loads on the runner. In some cases, fatigue cracks appear at the stress concentration location of the runner. This paper studied the dynamic stresses of a pump-turbine runner during load rejection process in turbine mode using finite element method. The hydraulic loads were obtained from CFD analysis, and the clearance flow was taken into consideration in the CFD simulation. The variation of performance characteristics was calculated through the one-dimensional method of characteristic (1D-MOC). The results show that the pressure on outer surfaces of runner changed the stress of the runner, and the rotation rate had a great influence on the dynamic stresses of the runner.